Pengaruh Organizational Citizenship Behavior (OCB) dan Gaya Kepemimpinan Terhadap Kinerja Guru di Madrasah Aliyah Al- Bairuny Jombang - Taqiyuddin, Akhmad; Hidayah, Nur (Business and Economic Publication, 2023)
This study aims to determine the effect of Organizational Citizenship Behavior (OCB) and Leadership Style on Teacher Performance at Madrasah Aliyah Al-Bairuny Jombang. The type of research used in this study is a type of quantitative research with associative methods. Source of data used is primary data. The technique used for sampling is Non Probability Sampling and using a saturated sampling technique with a total of 35 respondents. The data collection method uses a Likert Scale model questionnaire. The results showed that Organizational Citizenship Behavior (OCB) had no significant effect on teacher performance. Leadership style has an influence on the performance of MA Al-Bairuny Jombang teachers. The ability of several independent variables to influence the dependent variable is 43.2% and the remaining 56.8% is influenced by other factors outside of this study.Keywords:Organizational Citizenship Behavior (OCB), Leadership Style, Performance.